Development and performance evaluation of a poultry waste management technique using gravity sand filter - Akpenpuun, T. D.; Adeniran, K. A.; Akinyemi, B. A.; Ologun, O. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
The research aimed at developing and evaluating a poultry waste management technique using gravity sand filter. Poultry waste slurry prepared in a mixing tank was intermittently applied uniformly to the surface of a filter bed using a spreader as dosing technique. Two different types of configurations were designed for the filter bed. Single media bed consisted of 150mm depth of silica sand with average particle diameter of 0.5mm. Dual media bed consisted of 100mm depth of granulated charcoal with average particle diameter of 1.0mm and 50mm of silica sand with average particle diameter of 0.5mm. Design considerations important to achieving this level of treatment include; pretreatment, media characteristics, hydraulic and organic loading rates and filter dosing techniques. Each sand filter configuration was operated daily for a period of 12days. The following data were collected on a daily basis: Volume of effluents (mm3), hydraulic residence time (Hours), unit filter run volume (m3/m2), filtration rate or filtration velocity (mm/hr). Head loss on the filter was calculated using Carmen-Kozeny equation for uniform sand bed. Laboratory investigations showed that effluent from the filter had biological oxygen demand (BOD5), total suspended solids (TSS), total dissolved solids (TDS), and turbidity range between1.98 – 12.08 mg/L, 20.75 – 30.20 mg/L, 29.40 – 34.40 mg/L and 5.10 – 6.20 NTU.